Determination and Safety Evaluation of Heavy Metals in Canned Fish from Liaoning Province - Gu, Jiali; Lou, Yu; Zhao, Gang (Asian Journal of Chemistry, 2014)
The concentrations of seven heavy metal elements, e.g., Cd, Cr, Cu, Fe, Pb, Sn and Zn in canned fish from Liaoning province were determined by graphite furnace atomic absorption spectrometry after using microwave digestion techniques. Relative standard deviations (RSD) were 0.76-5.65 % and recoveries were 90-110 %. The results indicated that significant difference of elemental concentrations existed among the examined fish species. The concentrations of Cr, Cu, Pb and Zn in all the examined canned fish were below the maximum levels set by food-safety law and the concentrations of Cd in canned sardines and yellow croaker were above the maximum level. The concentrations of all the heavy metals in examined canned fish were lower than provisional tolerable weekly intake, so it may be concluded that canned fish from Liaoning province were edible, but necessary to reduce intake of canned sardines and yellow croaker.